2012
DOI: 10.1371/journal.pntd.0001873
|View full text |Cite
|
Sign up to set email alerts
|

CT694 and pgp3 as Serological Tools for Monitoring Trachoma Programs

Abstract: BackgroundDefining endpoints for trachoma programs can be a challenge as clinical signs of infection may persist in the absence of detectable bacteria. Antibody-based tests may provide an alternative testing strategy for surveillance during terminal phases of the program. Antibody-based assays, in particular ELISAs, have been shown to be useful to document C. trachomatis genital infections, but have not been explored extensively for ocular C. trachomatis infections.Methodology/Principal FindingsAn antibody-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
170
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 106 publications
(179 citation statements)
references
References 24 publications
7
170
0
2
Order By: Relevance
“…Since chlamydiae can complete their biosynthesis inside the inclusion, any chlamydial proteins that are secreted outside the inclusion may be used by chlamydial organisms as virulence factors for interaction with the infected host. Second, Pgp3 is an immunodominant antigen in women who have acquired chlamydial infection via either the genital tract (42,43) or the ocular route (38,44). In general, chlamydia-secreted proteins are likely to be more immunogenic (43).…”
Section: Figmentioning
confidence: 99%
“…Since chlamydiae can complete their biosynthesis inside the inclusion, any chlamydial proteins that are secreted outside the inclusion may be used by chlamydial organisms as virulence factors for interaction with the infected host. Second, Pgp3 is an immunodominant antigen in women who have acquired chlamydial infection via either the genital tract (42,43) or the ocular route (38,44). In general, chlamydia-secreted proteins are likely to be more immunogenic (43).…”
Section: Figmentioning
confidence: 99%
“…Depending on the country, serum was prepared from whole blood by centrifugation, or serum was eluted from DBS as previously described. 13,14 TT (Massachusetts Biologic Laboratories, Boston, MA) was coupled to SeroMap microspheres (Luminex Corp., Austin, TX) at the Centers for Disease Control and Prevention (CDC) with 12.5 μg of toxoid per 12.5 × 10 6 beads in buffer containing 50 mM 2-(N-morpholino) ethanesulfonic acid and 0.85% NaCl at pH 5.0, as previously described. 13,15 Serum samples were diluted 1:400 and assayed in duplicate for IgG (along with control sera) against multiple bacterial, viral, and parasitic disease antigens at CDC in Atlanta, GA, or the Kenya Medical Research Institute (KEMRI) in Nairobi, Kenya, using the conditions previously described.…”
mentioning
confidence: 99%
“…The first was an enzyme-linked immunosorbent assay (ELISA) assay that measured antibodies against the Ct antigen Pgp3 5, 6 . This tool has been used to assess transmission of both urogenital 7 and ocular 8 infections, including the study on Kiritimati Island, where we showed that there were strong associations between Ct infection, TF and anti-Pgp3 antibody levels. We also observed a rapid increase in Pgp3 seroprevalence throughout childhood years in that population 4 .…”
Section: Introductionmentioning
confidence: 94%